ANALISIS STRATEGI PEMASARAN MENGGUNAKAN METODE QUANTITATIVE STRATEGIC PLANNING MATRIX (QSPM): (Studi Kasus Pada Rumah Batik Minang Panyakalan) - Biiznillah Alifa Sya'nindita (2022)
Rumah Batik Minang Panyakalan is an business that was established in 2009, leading business engaged in batik craft in Solok Regency which have various motifs /designs with Minangkabau characteristics. Sales at the Rumah Batik Minang Panyakalan have decreased due to the impact of covid-19 and the Rumah Batik Minang Panyakalan does not yet have the right marketing strategy in order to survive the covid-19 pandemic. Therefore, the design of the right marketing strategy is needed to overcome the obstacles that exist in the company. The first step taken is the input stage, namely identifying the attributes of internal factors and external factors. Next is the matching stage, which is to match the type of strategy generated from the previous stage using the IE matrix, SPACE matrix, and SOAR. The result of this matching stage is a strategy that is suitable for the company to implement, namely market penetration, market development, and product development. Then, the last step is to determine the right alternative strategy to expand market share using QSPM where the alternative strategy is at the first level, namely creating an account for Rumah Batik Minang Panyakalan on social media and e-commerce to maximize sales and attract people's purchasing power with TAS value. of 4,512.